Controlling the Charge Transfer Mechanism and Efficiency by Means of Different C70 Regioisomeric Adducts. Issue 3 (22nd September 2020) - Plass, Fabian; Lukyanov, Daniil A.; Konev, Alexander S.; Kahnt, Axel; Amsharov, Konstantin Y.; Khlebnikov, Alexander F.; Guldi, Dirk M.
Abstract : Here, differences stemming from two newly synthesized electron donor–acceptor conjugates, α‐ or β‐regioisomeric adducts featuring orthogonal arrangements of an electron‐donating free‐base porphyrin (H2 P) and electron‐accepting C70, are reported. Key to a full‐fledged investigation in terms of both experiments and theory is the use of a rigid linker to separate the electron acceptor and donor. Both conjugates are experimentally investigated by means of femtosecond/nanosecond transient absorption measurements, which is further supported by radiation chemical studies based on pulse radiolysis. Significant regioisomeric differences are seen in the charge recombination kinetics, in general, which are as large as 1.4‐fold, and in the relative distributions of the charge recombination pathways, in particular, which reach nearly 1.5‐fold. Clearly, α‐regioisomers of C70 adducts are much better suited for the construction of future energy conversion systems than β‐regioisomers; a fact that relates to the superior electron delocalization within the carbon caps of C70 made out of "corannulenoid" fragments relative to the equator region of fullerenes featuring extended "phenanthrenoid" rings. Abstract : The mechanistic effects in molecular electron donor–acceptor systems are of high interest for the development of future biomimicking systems. The charge transfer mechanism of two newly synthesized C70 regioisomeric–based electron–donor acceptor conjugates is recorded in detail, resulting in significant but tunable differences acting as a guidance in using larger fullerenes in solar energy conversion schemes.